Pengembangan Media Pembelajaran Berbasis Sistem Presensi Face Recognition Integrasi GPS MTS Daarul Hikmah - Ahmad Asyidqi; Yasin Efendi; Mahbubul Wathoni; Sari Palestina (MES Bogor, 2026)
This study aims to develop a digital attendance system-based learning media integrated with face recognition technology and Global Positioning System (GPS) to support the assessment of students' discipline and responsibility at MTs Daarul Hikmah. The background of the study is based on the problem of using a manual attendance system that is prone to manipulation and is less effective in supporting technology-based learning. This study uses a research and development method (R&D) with the ADDIE model consisting of five stages, namely: Analysis, Design, Development, Implementation, and Evaluation. The development results show that the digital attendance system is able to automatically record student attendance based on facial verification and GPS location when attendance is carried out. The system was developed using the AppSheet platform connected to Google Spreadsheet as a database. Validation was carried out by material experts, media experts, and student responses, which showed an average feasibility percentage of 91.1%, including the